Cytoplasmic expression of UTP23 promotes colorectal cancer progression: UTP23 promotes colorectal cancer - E, Fang; Qian, Lili; Tang, Jinlong; Tong, Zhaowei (Cellular and Molecular Biology, 2024)
UTP23 (UTP23 small subunit processome component) plays a pivotal role in the intricate processing and maturation of the small subunit of ribosomes within the nucleolus. In cases of nucleolar stress, such as those observed in certain tumor cells, the aberrant nucleolar organization and structure can lead to the translocation of nucleolar proteins into the nucleus or cytoplasm, consequently impacting the physiological processes of the tumor cells through non-ribosome-related functions. Our investigation revealed altered localization of UTP23 protein in colorectal cancer clinical tissue samples. Upon analyzing UTP23 expression and its correlation with patient prognosis in a cohort of 143 colorectal cancer patients, the result suggested that high cytoplasmic expression pattern of UTP23 was occured in early-stage metastasis-free colorectal cancer and was significantly associated with poor prognosis. Furthermore, we demonstrated that cytoplasmic expression of UTP23 significantly promoted the metastatic and invasive capabilities of colorectal cancer cells, which was not showed in the nucleollcalised UTP23. Intriguingly, mass spectrometry result suggested that KRT5 bind to UTP23 and showed a regulatory influence on UTP23 metastatic potential in colorectal cancer cells. Conclusively, our study demonstrated that the localization of UTP23 play a key role in colorectal cancer metastatic progression, which may serve as a novel prognostic indicator.